Investigating the relationship between metabolic syndrome and the risk of developing dementia - Qureshi, DT (2024)
BACKGROUND: Metabolic syndrome (MetS) may be a risk factor for dementia, however, the relationship remains inconclusive. This thesis sought to clarify the association between MetS and incident dementia.